Regorafenib inhibits tumor progression through suppression of ERK/NF-κB activation in hepatocellular carcinoma bearing mice. Issue 3 (8th May 2018) - Weng, Mao-Chi; Wang, Mei-Hui; Tsai, Jai-Jen; Kuo, Yu-Cheng; Liu, Yu-Chang; Hsu, Fei-Ting; Wang, Hsin-Ell
Abstract : Regorafenib has been demonstrated in our previous study to trigger apoptosis through suppression of extracellular signal-regulated kinase (ERK)/nuclear factor-κB (NF-κB) activation in hepatocellular carcinoma (HCC) SK-Hep1 cells in vitro . However, the effect of regorafenib on NF-κB-modulated tumor progression in HCC in vivo is ambiguous. The aim of the present study is to investigate the effect of regorafenib on NF-κB-modulated tumor progression in HCC bearing mouse model. pGL4.50 luciferase reporter vector transfected SK-Hep1 (SK-Hep1/ luc2 ) and Hep3B 2.1-7 tumor bearing mice were established and used for the present study. Mice were treated with vehicle or regorafenib (20 mg/kg/day by gavage) for 14 days. Effects of regorafenib on tumor growth and protein expression together with toxicity of regorafenib were evaluated with digital caliper and bioluminescence imaging (BLI), ex vivo Western blotting immunohistochemistry (IHC) staining, and measurement of body weight and pathological examination of liver tissue, respectively, in SK-Hep1/ luc2 and Hep3B 2.1-7 tumor bearing mice. The results indicated regorafenib significantly reduced tumor growth and expression of phosphorylated ERK, NF-κB p65 (Ser536), phosphorylated AKT, and tumor progression-associated proteins. In addition, we found regorafenib induced both extrinsic and intrinsic apoptotic pathways. Body weight and liver morphology were not affected by regorafenib treatment. Our findings present the mechanism of tumor progression inhibition by regorafenib is linked to suppression of ERK/NF-κB signaling in SK-Hep1/ luc2 and Hep3B 2.1-7 tumor bearing mice.